SELF-LEADERSHIP AND INNOVATIVE WORK BEHAVIOR : THE MEDIATING EFFECT OF CREATIVE SELF-EFFICACY AMONG GOVERNMENT EMPLOYEES IN KESAMBI - Maysaroh, Iroh; Qodriah, Sari Laelatul; Risdianto, Risdianto (Politeknik Negeri Ambon, 2025)
Introduction: This study is driven by the inadequate level of inventive engagement among civil servants (PNS) in Kesambi District, as evidenced by their limited of involvement in national public service innovation initiatives, such as the West Java Innovation Competition and the Public Service Innovation Competition (KIPP). Methods: This quantitative study employs questionnaires administered to 53 civil servants, seleted using a saturated sample method. Results: The results indicate that self-leadership has a positve and significant influence on both creative self-efficacy and innovative work behavior. Moreover, creative self-efficacy has a substantial influence on innovative work behavior. This study's principal finding is that creative self-efficacy substantially mediates the connection between self-leadership and innovative work behavior.Conclusion and suggestion: This suggests that civil servants who can self-lead have greater confidence in their creative skills, hence augmenting their inventive conduct in the workplace. Consequently, enhancing self-leadership and creative self-efficacy ought to be a strategic priority in cultivating the capabilities of government personnel. Keywords: Self-Leadership, Creative Self-Efficacy, Innovative Work Behavior.